VERIFICATION OF LAMINATE COMPOSITEPLATE SIMULATION UNDER COMBINED LOADINGS THERMALSTRESSES (Journal of Engineering, 2024)
This study deals with thermal cyclic loading phenomena of plates which were fabricated from composite materials (woven roving fiber glass + polyester) were exposed to (75 C°) temperature gradient thermal shock for ten times in different stage of conditioning times due to the effect of thermal fatigue using the method of Levy solution and compared these results with both results from experimental published work and (ANSYS Ver. 9) program. A composite laminate plate with fiber volume fraction (υf =25.076%) is selected in this study and applying the combined loadings like bending moment (Mo), and in-plane force (Nxx) beside the effect of thermal fatigue. It involves multi theoretical and finite element fields; but the theoretical one contains the derived equation of stresses distribution and evaluating the normal deflection of a middle point for dynamic analysis applying different boundary conditions for heating and cooling. The main present numerical results for a composite plate with (80%) fiber volume fraction claim that the relative reduction in normal deflection and dynamic load factor are (78.593%) and (9.421%) during cooling to (-15 respectively.